Is There a Correlation between New Scoring Systems and Systemic Inflammation in Stable Bronchiectasis? - Hikmet Coban; Adil Can Gungen (Canadian Respiratory Journal)
Aim. The present study aimed to investigate the relation between FACED and BSI scores, which were developed to measure the severity of bronchiectasis, and systemic inflammation in patients with stable bronchiectasis. Methods. FACED and BSI scores of 117 patients with stable bronchiectasis were calculated. The correlations between mean scores and CRP levels, leukocyte count, and neutrophil/lymphocyte ratio were investigated. Findings. Mean BSI and FACED scores were 7.2 ± 5.2 and 2.1 ± 1.8, respectively. The severity of bronchiectasis as determined based on BSI and FACED increased significantly with increasing levels of CRP in patients with stable bronchiectasis (p=0.001 and p=0.027, resp.). No significant changes were found in leukocyte count (p=0.72 and p=0.09, resp.) and N/L ratio (p=0.45 and p=0.71, resp.). BSI and FACED scores were significantly correlated with CRP but not with leukocyte count or N/L ratio. Conclusion. In patients with stable bronchiectasis who are evaluated based on FACED and BSI scores, CRP can be a useful biomarker as a direct indicator of the severity of systemic inflammation.